INTEGRATION OF AI AND CLOUD TECHNOLOGIES IN HEALTHCARE: A COMPREHENSIVE FRAMEWORK FOR CAREER DEVELOPMENT AND PORTFOLIO ENHANCEMENT - Praveen Kumar Valaboju (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the integration of artificial intelligence (AI) and cloud technologies in healthcare, focusing on the skills and strategies necessary for professionals to excel in this rapidly evolving field. Through a comprehensive analysis of current literature and industry trends, we identify key technologies driving innovation, including CI/CD automation, Kubernetes for scalable infrastructure, cloud-based document management systems, and AI-powered diagnostic tools. The article highlights the importance of practical experience in these areas and provides a framework for building a competitive portfolio that showcases proficiency in solving healthcare-specific challenges. Furthermore, we explore career development strategies, emphasizing continuous learning, professional networking, and contributions to open-source projects. Our findings suggest that professionals who combine technical expertise in AI and cloud computing with a deep understanding of healthcare contexts are well-positioned to drive significant advancements in patient care, operational efficiency, and data security. This article contributes to the growing body of knowledge on technology integration in healthcare and offers valuable insights for both aspiring and established professionals seeking to navigate this dynamic landscape.